Determining the optimal distribution of maintenance branches of the General Directorate of Public Works on the roads of the Algerian states using the concentration factor for decision theory - Bouragba, Kouider; Raache, Kamal; Mebkhouta, Ahmad (Journal of Human Sciences, 2022)
The study aimed to determine the optimal distribution between the length of roads in each Of the Algerian states and the number of maintenance branches located in it,where the gene coefficient and the relative scale and scale of difference were used to determine the shortage and surplus to redistribute them according to the length of the roads, the study found that there is an unfair distribution between the length of the roads in each state and the number of maintenance branches allocated to it where it was found that 45 Algerian states contain a surplus of maintenance branches while there are 3 states suffer from a severe shortage of branches of maintenance, the most prominent of these states that suffer from severe shortage is the state of Skikda with a need of 299 maintenance branches because it is the first state in national level in terms of the length of roads in it, as the study reached an optimal distribution of branches of road maintenance across the entire national territory by using the standard of difference and was achieved using the descriptive and analytical method to reach it.